(untitled) (Advancements in Homeopathic Research, 2026)
Osteoarthritis (OA) is a slow, progressive, degenerative disease, affecting the articular cartilage of the joints and ultimately causing its destruction leading to disability. The most commonly affected joint is knee. OA of the knee is a major cause of mobility impairment, particularly among females. Various studies have demonstrated the beneficial effect of Homoeopathic treatment in cases of Knee OA. Homoeopathic approach of totality of symptoms has given significant results in this area as well as some commonly therapeutically indicated medicines also have given good results. AIM • To assess the effectiveness of homoeopathic medicines in pain management in cases of Knee Osteoarthritis. Objectives • To assess the effectiveness of homoeopathic medicines as compared to placebo in pain management in cases of Knee Osteoarthritis on the basis of Pain Visual analog scale (VAS). • To assess the effectiveness of homoeopathic medicines as compared to placebo in pain management in cases of Knee Osteoarthritis on the basis of Knee Injury and Osteoarthritis Outcome Score (KOOS). • To assess the predominant miasm in cases of Knee Osteoarthritis with reference to concepts of C.F.S Hahnemann, J.T. Kent, J.H. Allen, H.A. Roberts. Materials & Methodology: A Randomized single blind placebo controlled study was conducted at Dr. Madan Pratap Khunteta Homoeopathic Medical College & Hospital, Jaipur during the period of August 2018 to July 2019. 70 cases (Both Groups A and B) of Knee Osteoarthritis were selected as per inclusion and exclusion criteria and randomly allocated to two treatment groups. In Group A (n=35 cases) cases were treated with individualised homoeopathic medicines along with physiotherapy selected on the basis of the totality